Kolmogorov-Type Inequalities for Fractional Derivatives on the Half Line - Levchenko, D. A. (Ukrains’kyi Matematychnyi Zhurnal, 2014)
We obtain new sharp Kolmogorov-type inequalities for the fractional derivatives of functions defined on the half line.